Naipaul, V. S. A máscara da África: vislumbres das crenças africanas. Tradução: Marcos Bagno. São Paulo: Companhia das Letras, 2011. 288 p. DOI: 10.5212/MuitasVozes.v.1i1.0010 - Pinto, Julio Pimentel (Muitas Vozes, 2012)
.